2011
DOI: 10.1007/s11096-011-9488-z
|View full text |Cite
|
Sign up to set email alerts
|

Design and test of preference for a new prescription medication label

Abstract: New prescription labels were favored over existing labels by all stakeholders, for content, convenience and cosmetic appearance. The results may help in making labels more user-friendly and addressing problem areas in labels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…However, a number of earlier studies support the acceptability and preference of the many patient-centered modifications under study. [34][35][36] The majority of patients did not receive a benefit from the PCL, but in no instance did we find that it performed worse than standard labeling. As the intervention involved subtle modifications to pharmacy-generated labeling that could be readily put into practice, set to scale, even small increases in proper use and adherence among subgroups of consumers might yield a cost benefit.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of earlier studies support the acceptability and preference of the many patient-centered modifications under study. [34][35][36] The majority of patients did not receive a benefit from the PCL, but in no instance did we find that it performed worse than standard labeling. As the intervention involved subtle modifications to pharmacy-generated labeling that could be readily put into practice, set to scale, even small increases in proper use and adherence among subgroups of consumers might yield a cost benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Presented with a choice, most patients prefer instructional leaflets and prescription labels that include indications to those that don't include indications. 4 Knowledge of the indication can also empower patients to question the necessity of a medication.…”
Section: Incorporating Indications Into Medication Ordering -Time To mentioning
confidence: 99%
“…Previous qualitative studies, which have focused on the content and design of the dispensed medicine label, have found that 28% to 91% of patients were in favour of documenting the indication on the dispensed medicine label [ 7 13 ]. Additionally, two literature reviews on best label practice, comprising the results of 135 individual studies, found that consumers want the indication documented on the dispensed medicines labels to better understand/remember what the medications are used for [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%